Beyond EZH2: is the polycomb protein CBX2 an emerging target for anti-cancer therapy?. (3rd July 2019) - Jangal, Maïka; Lebeau, Benjamin; Witcher, Michael
ABSTRACT: Introduction : Epigenetic modifications are important regulators of transcription and appropriate gene expression answering an environmental stimulus. In cancer, these epigenetic modifications are altered, which impact the transcriptome, promoting initiation and cancer progression. Thus, targeting epigenetic machinery has proven to be an efficient cancer therapy. Areas covered : We review CBX2 as a therapeutic target. CBX2 is a polycomb protein, responsible for polycomb-repressive complex 1 (PRC1) targeting to chromatin via recognition of the repressive mark H3K27me3. Mechanistically, CBX2 overexpression may be implicated in poor survival by maintaining cancer stem cells in an undifferentiated state and via repression of tumor suppressors. We discuss strategies used to target CBX proteins and provide insights into biomarker considerations that may be important when targeting CBX family members for anti-cancer therapy. Expert opinion : CBX2 inhibition is a promising approach for the targeting of polycomb complexes in the cancer stem cell niche. However, extensive optimization of the current field of small molecules targeting CBX family proteins will be critical to reach in vivo, or clinical, utility.